APPLICATION OF CHROMATOGRAPHIC COLUMNS WITH AMIDE SORBENT TO THE ANALYSIS OF PLATINUM COORDINATION COMPOUNDS - A. S. Osipov; O. A. Popova; N. V. Raslyakova; L. L. Koshimyakina (Разработка и регистрация лекарственных средств, 2019)
It was established that chromatographic column with amide sorbent (XBridge Amide) could be applied to the analysis of Pt (II) coordination compounds. The compounds could be analyzed by both reversed-phase chromatography [mobile phase: MeCN - Н2О (2:98)] and hydrophilic interaction liquid chromatography [mobile phase: MeCN - Н2О (90:10)]. The analytes were better resolved for hydrophilic interaction liquid chromatography. The properties of the amide columns differed substantially for analysis of Pt (II) coordination compounds using mobile phases with more 80% MeCN. Sorption of the Pt compounds to the amide columns at high MeCN contents was due to specific coordination interactions between the Pt atom and sorbent amides.